"Donorship" and strategic policy‐making: Germany's Middle Eastern and North African aid programme since the Arab uprisings. (6th April 2020) - Furness, Mark
Abstract: Motivation: Germany's official aid to Middle Eastern and North African (MENA) countries has more than doubled since 2011, ostensibly to support their own responses to development and humanitarian challenges following the Arab uprisings. The dramatic increases in aid have not been accompanied by a public strategy setting out Germany's objectives in the region, and the role of aid in conjunction with other policy tools in achieving them. Purpose: What strategic objectives does the German government have for its MENA aid, and have these objectives changed in response to the Arab uprisings? Does the practice of Germany's aid spending actually address development and humanitarian challenges in the MENA region, as these are defined by MENA countries themselves? In order to address these questions, this article develops key insights from the historical institutionalist and aid effectiveness literature that explain strategic policy‐making in complex decision‐making systems. Approach and Methods: Two propositions are discussed in a structured review of the policy and practice dimensions of Germany's MENA aid programme: first, that Germany's aid and foreign policy system has not been able to articulate a clear strategy due to political differences and bureaucratic inertia; and second that the priorities tend to favour German and European security interests rather than the region's own development and humanitarian priorities. Findings: The analysis reveals that, while new priorities for development co‐operation in response to the Arab uprisings have been set, Germany's MENA aid programme shows signs of policy incoherence and fragmentation. This is unlikely to change without a "whole‐of‐government" strategy for Germany's MENA engagement. Furthermore, while there is little evidence of purposeful securitization of aid, short‐term stability has been privileged over support for political change. Policy Implications: A whole‐of‐government strategy based on the Sustainable Development Goals could balance German interests with the MENA region's development priorities, ironing out the most problematic incoherencies, and thereby increasing partner country ownership.